PENDAMPINGAN PENGELOLAAN SAMPAH BOTOL PLASTIK DALAM MENDUKUNG PROGRAM PEMBANGUNAN BERKELANJUTAN DI KELURAHAN TLOGOSARI WETAN KOTA SEMARANG - Masvika, Hendra; Purwanto, Purwanto; Wanto, Sri; Khasanah, Nur (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
The use of plastic materials is commonly encountered in everyday life, ranging from food and beverage packaging to containers for various tools and materials. Plastic is chosen because it is easy and practical to use. However, excessive plastic use can lead to the accumulation of plastic waste, resulting in environmental pollution. Given the lack of understanding and concern among the public regarding ecological preservation and support of sustainable development goals (SDGs), efforts are needed to increase environmental awareness and concern through accompanying activities in the sustainable management of plastic bottle waste. The objective of this community service activity (PkM) is to provide support in the management of plastic bottle waste to support SDGs in the Tlogosari Wetan Sub-district, Pedurungan District, Semarang City. The partners involved are members of the community and the officials of the Tlogosari Wetan Sub-district. The implementation method used is Participatory Action Research (PAR), which involves partners managing plastic bottle waste from sorting to disposal. Partners were given education through lectures and question-and-answer sessions, as well as demonstrations in plastic bottle waste management. This mentoring activity resulted in a 70% increase in public understanding and awareness, supported by 80% of the community expressing commitment to sorting plastic bottle waste as a form of sustainable waste management. The community service activity concluded with the handover of plastic bottle waste containers to the community.